Didactic and Methodical Qualities of Isidor Bajić’s Textbook 'A Theory of a Notation Singing' - Ilić, Petar M. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
This work elaborates on a didactic and methodical qualities of the book A Theory of a Notation Singing by Isidor Bajić. As a literature for elementary music education, it has been initially published in 1904, under the title A Theory of an Accurate Notation Singing. After the first, then came the second amended edition in 1912 named A Theory of a Notation Singing. At the beginning of the twentieth century, there were no music books nor instructions approved by the Serbian Ministry of Education that could serve as notation singing literature. Because of that, Isidor Bajić arranged for a book with elementary theoretic and practical basis of solfege education and music theory. The contents had been grouped into sections of basic pedagogy of accurate notation singing. The main courses of the book encompass music theory, rhythm, melody, and the basis of vocal singing technique. This book is not included in the recommended literature for solfege education and music theory for the elementary music education in Serbia. Based on that, the aim of this work is to highlight possible usability and implementation of one of the first methodological books for a notation education within the Serbian language realm. The implementation of the book A Theory of Notation Singing would broaden the official set of listed literature within the basic solfege education domain. This work, through a method of theoretical analysis, employs didactic and methodological apparatus, textual and notation content of a second amended volume.
Keywords: instructive melodic examples; A Theory of Notation Singing; Isidor Bajić; vocal technique